Ferroptosis-related genes as prognostic markers for survival and immunotherapy in triple-negative breast cancer: analysis of public databases and a single institution - Yizhao Xie; Zhonghua Tao; Biyun Wang; Yannan Zhao; Xinyu Chen; Bin Li; Jinyan Wang; Guangliang Chen; Xichun Hu (Therapeutic Advances in Medical Oncology)
Background: Ferroptosis plays a vital role in cancer development and treatment. The relationship between ferroptosis-related genes and breast cancer prognosis, as well as immunotherapy outcomes, remains unknown. Objectives: To evaluate the prognostic value of ferroptosis-related genes in breast cancer. Methods: We conducted differential expressions and prognostic analysis for ferroptosis-related genes on public databases and breast cancer patients in our center and analyzed their predictive value for immunotherapy of breast cancer patients. Results: We identified prognostic ferroptosis-related genes, constructed a nomogram, and validated key genes using patient data from our center. We also investigated ferroptosis-related genes significantly associated with immune infiltration and identified FTH1 as a promising biomarker for triple-negative breast cancer immunotherapy. Conclusion: Ferroptosis-related genes had potential prognostic value and predictive value for breast cancer immunotherapy.